Emocjonalne korelaty nierówności w relacjach rodzinnych – od ambiwalencji społecznej do ambiwalencji emocjonalnej - Frąckowiak-Sochańska, Monika (Człowiek i Społeczeństwo, 2025)
The paper aims to analyze the links between structural inequality, inequality within the family, and emotional ambivalence. The theoretical foundations of the article are the structural ambivalence theory and the critical concept of family ties by Ingrid A. Connidis and Julie A. McMullin in conjunction with Theodor Kemper’s power-status theory. Previous empirical research on ambivalence in family relationships identifies relations particularly prone to ambivalence. However, they lack more detailed data on how individuals experience ambivalence and how they cope with it. The author’s findings aim to fill this knowledge gap. Based on qualitative research, in-depth interviews with a sample of 22 people with at least one ambivalent family relationship, aged between twenty and sixty, 13 women and 9 men, representing diverse socio-demographic categories, the author discovered that family relations particularly prone to ambivalence are associated with 1) unequal transfer of support, 2) unequal sharing of responsibilities for caring for dependent family members, and 3) increasing inequality despite initial equality. The article reconstructs the configurations of ambivalent emotions in the above relationships. The ways of coping with ambivalence reconstructed from data analysis allow the individual to temporarily reduce tension and maintain a sense of agency but simultaneously stabilize the status quo, as they do not fundamentally change the unequal relationship.